Neuromuscular adjustments of the quadriceps muscle after repeated cycling sprints. - Olivier Girard (Public Library of Science (PLoS), 2013)
Purpose This study investigated the supraspinal processes of fatigue of the quadriceps muscle in response to repeated cycling sprints. Methods Twelve active individuals performed 10 × 6-s "all-out" sprints on a cycle ergometer (recovery = 30 s), followed 6 min later by 5 × 6-s sprints (recovery = 30 s). Transcranial magnetic and electrical femoral nerve stimulations during brief (5-s) and sustained (30-s) isometric contractions of the knee extensors were performed before and 3 min post-exercise. Results Maximal strength of the knee extensors decreased during brief and sustained contractions (~11% and 9%, respectively; P<0.001). Peripheral and cortical voluntary activation, motor evoked potential amplitude and silent period duration responses measured during briefs contractions were unaltered (P>0.05). While cortical voluntary activation declined (P<0.01) during the sustained maximal contraction in both test sessions, larger reductions occurred (P<0.05) after exercise. Lastly, resting twitch amplitude in response to both femoral nerve and cortical stimulations was largely (> 40%) reduced (P<0.001) following exercise. Conclusion The capacity of the motor cortex to optimally drive the knee extensors following a repeated-sprint test was shown in sustained, but not brief, maximal isometric contractions. Additionally, peripheral factors were largely involved in the exercise-induced impairment in neuromuscular function, while corticospinal excitability was well-preserved.